2005
DOI: 10.1111/j.1399-3054.2005.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient versus reduced UV‐B radiation on high arctic Salix arctica assessed by measurements and calculations of chlorophyll a fluorescence parameters from fluorescence transients

Abstract: Document VersionPublisher's PDF, also known as Version of record Link back to DTU Orbit Citation (APA): Albert, K. R. (2005). Effects of ambient versus reduced UV-B radiation on high arctic Salix arctica assessed by measurements and calculations of chlorophyll-a fluorescence parameters from fluorescence transients. Physiologia Plantarum, 124,[208][209][210][211][212][213][214][215][216][217][218][219][220][221][222][223][224][225][226] Effects of ambient versus reduced UV-B radiation on high arctic Salix arcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 85 publications
5
38
0
Order By: Relevance
“…Plant responses to UV-B tend to be subtle and species-specific, especially when studies are conducted outside under realistic spectral regimes. Responses to elevated and ambient UV-B include increases in DNA-damage and antioxidant response [2], alterations in plant morphology and architecture [3,4], slight reductions in chlorophyll fluorescence parameters associated with photosystem II [PSII; 5,6] and lower biomass accumulation [7][8][9][10][11]. The most common response of field-grown plants to elevated and ambient levels of UV-B appears to be an increase in concentrations of UV-absorbing phenolics [1,12,13] that may ameliorate potentially damaging UV-B before it reaches sensitive chromophores [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Plant responses to UV-B tend to be subtle and species-specific, especially when studies are conducted outside under realistic spectral regimes. Responses to elevated and ambient UV-B include increases in DNA-damage and antioxidant response [2], alterations in plant morphology and architecture [3,4], slight reductions in chlorophyll fluorescence parameters associated with photosystem II [PSII; 5,6] and lower biomass accumulation [7][8][9][10][11]. The most common response of field-grown plants to elevated and ambient levels of UV-B appears to be an increase in concentrations of UV-absorbing phenolics [1,12,13] that may ameliorate potentially damaging UV-B before it reaches sensitive chromophores [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of UV-B on plants is studied experimentally by either using filters to attenuate the UV-B exposure or by using supplementary lights to increase the UV-B exposure (e.g., Albert et al, 2005;Ballare et al, 2001;Bassman et al, 2001;Day and Neale, 2002;Flint et al, 2003;Qaderi and Reid, 2005;Rousseaux et al, 2004;Searles et al, 1995;Tevini, 2004). These reports reveal a great variety of UV-B effects on photosynthesis, morphology, and growth.…”
Section: Tmentioning
confidence: 99%
“…Bredahl et al (2004, p.363) reported higher maximal photochemical efficiency (measured as the chlorophyll fluorescence parameter Fv/Fm) under UV-B reduction. Quantum efficiencies, specific and phenomenological fluxes were all enhanced by UV exclusion indicating a negative impact of ambient UV on all of these parameters in the plant species (Albert, Mikkelsen, & Ro-Poulsen, 2005, Albert, Mikkelsen, & Ro-Poulsen, 2008, Albert et al, 2010, p.1542Kataria et al, 2013, p.140). The increases in the efficiency that an absorbed photon will be trapped by the PSII reaction centre with the resultant reduction of QA to QA -(ET0/ABS = FV/FM) and the efficiency that an electron residing on QA-will enter the intersystem electron transport chain (ET0/TR0) were observed in reduced UV-B.…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%
“…The UV-exclusion experiments showed that a reduction of the ambient UV-B level resulted in decreased content of UV-B absorbing compounds and lower stress level indicated by increased maximal quantum yield (FV/FM) and Performance Indexes (PI) (Bredahl, Ro-Poulsen, Mikkelsen, 2004;Albert et al, 2005Albert et al, , 2008Albert et al, , 2010Kataria et al, 2013, p.140). Bredahl et al (2004, p.363) reported higher maximal photochemical efficiency (measured as the chlorophyll fluorescence parameter Fv/Fm) under UV-B reduction.…”
Section: Chlorophyll Fluorescencementioning
confidence: 99%